2019
DOI: 10.31557/apjcp.2019.20.2.369
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Cancer in Khon Kaen, Thailand: Analysis of 1990-2014 Incidence Data and Prediction of Future Trends

Abstract: Background:Cervical cancer is the second most common cancer of women in Thailand. There have been no reports of incidence and future in Khon Kaen, a province in northeastern Thailand, where the relatively high prevalence gives evaluation of cervical cancer screening a high priority. Objectives:To determine cervical cancer incidence rates in Khon Kaen for 1990–2014 and predict future trends until 2029. Methods:Cancer incidence data from the Khon Kaen population-based cancer registry were analyzed and age-standa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
0
5
1
Order By: Relevance
“…Globally, the cervical cancer ASIR declined, albeit some countries like East Asia and Southern sub-Saharan Africa showed an upward trend (Zhang et al, 2019)). Our study revealed a declining trend with EAPC -3.0% which was marginally higher than EAPC reported in Khon Kaen Thailand (-2.8.%; 1990-2014) (Saenrueang et al, 2019). The decline of cervical cancer is primarily a result of the change in preventive measures such as behaviours of social culture factors, improvement in health care services, enhancement in the literacy rate, delay in marriage age, and family planning behaviours (Vu et al, 2018).…”
Section: Discussioncontrasting
confidence: 55%
“…Globally, the cervical cancer ASIR declined, albeit some countries like East Asia and Southern sub-Saharan Africa showed an upward trend (Zhang et al, 2019)). Our study revealed a declining trend with EAPC -3.0% which was marginally higher than EAPC reported in Khon Kaen Thailand (-2.8.%; 1990-2014) (Saenrueang et al, 2019). The decline of cervical cancer is primarily a result of the change in preventive measures such as behaviours of social culture factors, improvement in health care services, enhancement in the literacy rate, delay in marriage age, and family planning behaviours (Vu et al, 2018).…”
Section: Discussioncontrasting
confidence: 55%
“…A decrease was projected in all geographic zones except the North-East during 2012-2025 (Virani et al, 2017). However, a decreasing trend in incidence of cervical cancer in Khon Kaen was evident from 1990 to 2014 with a prediction of continuous decrease until 2029 (Saenrueang et al, 2019). Cervical cancer incidence in Songkhla peaked around 1998-2000 and then dropped by 4.7% per year (Sriplung et al, 2014).…”
Section: Healthy Life-style Promotionmentioning
confidence: 99%
“…Cervical cancer (CC) was the fourth most common cancer in women worldwide, following breast, colorectal, and lung cancers based on GLOBOCAN 2018 estimates (Farahat et al, 2021;Shivamurthy et al, 2022). There were an estimated 311,365 global deaths from CC and 569,847 new cases, or incidence of 15.1 per 100,000 women, in 2018 (Anfinan and Sait, 2020).…”
Section: Introductionmentioning
confidence: 99%